Culturalisation, Homogenisation, Assimilation? Intersectional Perspectives on the Life Experiences of Sami People with Disabilities - Fylling, Ingrid; Melbøe, Line (Scandinavian Journal of Disability Research, 2019)
Source at http://doi.org/10.16993/sjdr.575 . Sami people experience a wide range of challenges in their dealings with health and social services (Blix 2016). However, little is known so far about the circumstances for disabled people of a Sami background (Huuva 2014). Since previous research has shown that people with disabilities have poorer living conditions and fewer opportunities for social participation than the general population (Kittelsaa, Wik & Tøssebro 2015; Söderström & Tøssebro 2011), it would be reasonable to assume that disabled people of a Sami background may risk marginalisation along both dimensions or have a ‘double disadvantage’ (Wehmeyer 2007). Through narrative analysis of interviews with disabled Sami people, we discuss marginalisation processes faced by this category in their dealings with welfare services. We argue that research based on experiences from ethnic minorities are not sufficient analytical tools to understand the experiences of the Sami people. Rather than experiencing culturalisation (Fuentes 2015), disabled people of a Sami background still experience assimilation mechanisms when communicating with welfare services.